Grain yield of rice cultivars and lines developed in the Philippines since 1966 - Peng, S.; Laza, R.C.; Visperas, R.M.; Sanico, A.L.; Cassman, K.G.; Khush, G.S. (Wiley, 2000)
Genetic improvement in grain yield has been intensively studied in wheat (Triticum aestivum L.), barley (Hordeum vulgare L.), oat (Avena sativa L.), maize (Zea mays L.), and soybean [Glycine max (L.) Merr.]. Such information is limited in rice (Oryza sativa L.). The objective of this study was to determine the trend in the yield of rice cultivars–lines developed since 1966. Twelve cultivars–lines were grown at the International Rice Research Institute (IRRI) farm and the Philippine Rice Research Institute farm during the dry season of 1996. Seven cultivars–lines were grown at IRRI farm in the dry season of 1998. Growth analyses were performed at key growth stages, and yield and yield components were determined at physiological maturity. Regression analysis of yield versus year of release indicated an annual gain in rice yield of 75 to 81 kg ha−1, equivalent to 1% per year. The highest yields obtained with the most recently released cultivars was 9 to 10 Mg ha−1, which is equivalent to reported yields of IR8 and other early IRRI cultivars obtained in the late 1960s and early 1970s at these same sites. Therefore, the 1% annual increase in yield may not represent genetic gain in yield potential. The increasing trend in yield of cultivars released before 1980 was mainly due to the improvement in harvest index (HI), while an increase in total biomass was associated with yield trends for cultivars–lines developed after 1980. Results suggest that further increases in rice yield potential will likely occur through increasing biomass production rather than increasing HI.